2014
DOI: 10.4028/www.scientific.net/amr.939.361
|View full text |Cite
|
Sign up to set email alerts
|

Springback of Aluminum Alloy Sheet Metal and its Modeling

Abstract: Aluminum alloy sheet metals have been widely utilized for a light weight construction of automobile. However, Aluminum sheet metals still remain one of the difficult materials to predict the accurate final shapes after press forming processes, because of several mechanical weak features such as lower Youngs modulus, strong plastic anisotropy of yield stress, Lankford values, and so on. In order to solve the problems, the present author has developed a new constitutive model called Modified Yoshida-Uemori model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Ling et al [4] 2005 presented the process parameters of L-bending process such as die clearance, die radius, step heigh, step distace and their effects on spring-back by using the FEM. Takeshi Uemori et al 2010 [5] compared the FE simulation and experimental results of springback of draw bending and S-rail forming of 590 and 980 MPa steel sheets. Ogawa and Yoshida [6] 2011 investigated the effect of die-corner bottoming.…”
Section: Introductionmentioning
confidence: 99%
“…Ling et al [4] 2005 presented the process parameters of L-bending process such as die clearance, die radius, step heigh, step distace and their effects on spring-back by using the FEM. Takeshi Uemori et al 2010 [5] compared the FE simulation and experimental results of springback of draw bending and S-rail forming of 590 and 980 MPa steel sheets. Ogawa and Yoshida [6] 2011 investigated the effect of die-corner bottoming.…”
Section: Introductionmentioning
confidence: 99%
“…In most of cases of sheet stamping simulations, the criterion combined von Mise's yield criterion with an isotropic hardening model is utilized by default, however, it causes the serious errors of stress analysis due to the lack of description of the plastic anisotropy and the Bauschinger effect of sheet metals An appropriate choice of the combination is very important for an accurate sheet-metal stamping simulation [1][2][3] For that purpose, "Yoshida-Uemori model" has been proposed and its high capability in simulating cyclic behavior. The model has been already verified by comparing the numerical simulations with several evidences [4][5][6]. However, it was found that the verification of this model, especially the details of the non-proportional deformation behaviors, is not guaranteed for low yield point materials.…”
Section: Introductionmentioning
confidence: 99%